Long-term tree population growth can predict woody encroachment patterns - Robert K. Shriver; Elise Pletcher; Franco Biondi; Alexandra K. Urza; Peter J. Weisberg (Proceedings of the National Academy of Sciences, 2025)
Recent increases in woody plant density in dryland ecosystems—or “woody encroachment”—around the world are often attributed to land-use changes such as increased livestock grazing and wildfire suppression or to global environmental trends (e.g., increasing atmospheric carbon dioxide). While such changes have undoubtedly impacted ecosystem structure and function, the evidence linking them to woody encroachment is mixed, and the underlying processes are not fully understood. To clarify the role of demographic processes in changing woody plant abundance, we conducted a meta-analysis of tree age structures from 29 woodland populations across the interior western United States, estimating per-capita tree establishment rates over the last several hundred years using demographic models. We found only limited evidence of increases in per-capita tree establishment rates following 19th-century Euro-American settlement. On the contrary, our results showed that observed age structures dominated by young trees, often cited as evidence of woody encroachment driven by anthropogenic processes, can be largely predicted by a null model based only on steady, multiplicative tree population growth. Moreover, we demonstrated that tree establishment rates in the last century have mostly declined rather than increased, and they are currently at their lowest rates since at least 1600 CE. Our results suggest that a large part of modern increases in woodland tree establishment and density may in fact be a result of long-term population increases, and failing to consider the demographic processes underlying population growth can lead to an overestimation of settlement effects on stand structure.